Keragaman Serangga Hama dan Musuh Alami Lahan Pertanian Padi Organik (Oryza Sativa L) Desa Rowosari Kecamatan Sumberjambe Kabupaten Jember - Hari Purnomo; Moh. Dana Parawangsa (Jember University Press, 2023)
The application of organic rice farming systems is a solution to the negative impacts of using chemicals in the application of conventional farming systems. Organic rice cultivation cannot be separated from the presence of insect pests that attack cultivated plants. Naturally, in an ecosystem that is still good, natural enemies are already present in nature without human intervention. The existence of natural enemies in a field can suppress the existing population of insect pests, so that their presence is very helpful in maintaining the balance of the existing insect pest populations. The stability of insect populations in an agricultural ecosystem is largely determined by the high diversity of insect pests and natural enemies found in a field. Thus there is a need for research on the diversity of insect pests and natural enemies as information about which insect families are found on organic rice farming land in Rowosari Village, as well as a consideration for farmers in applying appropriate control methods. This study used yellow pan trap, sweep net and vacuum cleaner insect monitoring tools. The research was conducted on 3 observation plots in the organic rice fields of Tani Jaya II Group, Rowosari Village, Sumberjambe District, Jember Regency. Observations were made 10 times from the vegetative phase to the generative phase of rice aged 7 to 77 days after planting. Observational data were then identified and then analyzed using the Shanon-Wiener Diversity Index (H), Evenness Evenness Index (E), Simpson Dominance Index (D), and Margalef Species Richness Index (R). The results showed that there were 7 families of Pest Insects found on organic rice farming in Rowosari Village, including Pyralidae, Alydidae, Grylidae, Cicadellidae, Chrysomelidae, Acrididae, and Nymphalidae. Natural Enemy Insects found were 9 families including Coccinellidea, Coenagrionidae, Gomphidae, Penttomidae, Meoidae, Miridae, Ichneumonidae, Staphylinidae, and Sciomyzidae. Neutral insects found were as many as 4 families, including Muscidae, Vespidae, Tephritidae, and Drosophilidae. The population of insect pests and natural enemies of organic rice farming land in Rowosari Village is quite balanced with a Diversity Index (H') of 2.32 and Species Richness Index (R) of 2.98, Evenness index (E') of 0.77 which is in the almost even and Dominance (D) 0.13 which means not dominating.